Single-crystal X-ray diffraction, EMPA, FTIR and X-ray photoelectron spectroscopy study of narsarsukite from Murun Massif, Russia. (2nd January 2018) - Schingaro, E.; Mesto, E.; Lacalamita, M.; Scordari, F.; Kaneva, E.; Vladykin, F. N.
Abstract: A crystal chemical study of narsarsukite from the Murun alkaline massif, Russia has been carried out combining single-crystal X-ray diffraction, electron microprobe analyses, micro-Fourier transform infrared (FTIR) spectroscopy and X-ray photoelectron spectroscopy (XPS). The narsarsukite single crystals are tetragonal (space group I 4/ m ) with unit-cell parameters: 10.7140(1) ≤ a ≤ 10.7183(2) Å and 7.9478(1) ≤ c ≤ 7.9511(1) Å. The XPS analysis showed that Fe occurs in the mineral as Fe3+, whereas the FTIR spectrum showed that the sample studied is anhydrous. The average crystal chemical formula of the Murun narsarsukite is: Na2.04 K0.01 (V0.01 5+ Ti0.74 Zr0.01 Al0.01 Fe0.22 3+ Mg0.01 )1.00 Si4.00 (O10.74 F0.23 OH0.03 )11.00 . Structural disorder at octahedral and interstitial sites was modelled and also discussed in consideration of the main substitutional mechanism Ti 4+ + O 2– ↔ Fe 3+ + (F –, OH – ) active in the structure of the mineral.